Fracture behavior and acoustic emission characteristics of layered sandstone with a bedding-parallel crack - Liu, Kewei; Zou, Liansong; Guo, Tengfei; Guo, Can; Yang, Jiacai; Zhang, Yi (Theoretical and applied fracture mechanics, 2024)
•Fracture mode and AE characteristics of layered sandstone were analyzed.•Four division methods were adopted to identify crack types, and an optimal method was determined.•An optimal fracture criterion for predicting fracture toughness was determined. Bedding planes and cracks are widely found in natural rock mass, exerting a substantial effect on the stability and security of layered rock structures. Cracked straight-through Brazilian disc (CSTBD) tests were conducted to analyze the fracture mechanics of layered sandstone. Meanwhile, acoustic emission (AE) monitoring system was applied to reveal AE characteristics. Test results indicate that bedding planes substantially influence the strength and crack extension behaviors. Tensile failure along bedding planes corresponds to the lowest strength, and the highest strength is observed when failure appears perpendicular to the beddings. Three failure modes are recognized: bedding planes failure (θ = 0°), mixed failure (θ = 15°, 30°, 45°, 60°, and 75°), and matrix failure (θ = 90°). The b-value can be considered as a predecessor index of rock engineering instability, and fracture will occur when b-value achieves the minimum value. Comparing the proportions of tensile-shear crack obtained from four different classification methods, it is found that the average frequency (AF) and rise angle (RA) distribution acquired through the K-means clustering algorithm provides optimal results for identifying the tensile and shear crack types. Furthermore, the study reveals that the absolute value of mode I fracture toughness declines first and then increases with the θ growth, while mode II fracture toughness exhibits the opposite trend. Finally, the mixed-mode fracture mechanism of layered sandstone was analyzed, and results showed that the generalized maximum tangential stress (GMTS) criterion could produce better projections for fracture toughness and crack initiation orientations.